Pengaruh Tanggung Jawab Dan Konflik Terhadap Stres Guru Sekolah Dasar (SD) Negeri Se-Kecamatan Cileungsi Kabupaten Bogor - Erwin, Erwin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
The research was conducted to all teachers of elementary school districts Cileungsi regency of Bogor. By using a survey method with path analysis applied in testing hypothesis the number 80 teachers as sample was selected by using Slovin formula. Based on the results of data analysis in this research it is concluded: (1) the responsibility have negative direct effect to stress; (2) the conflict have positive direct effect to stress; (3) the responsibility have negative direct effect to conflict. The stress can be decreases through improvement of responsibility and to manage of conflict